Exploring the possibility of chemisorption of ethylene on graphene with and without defects - Parisa Alamdari; Farhad Sharif; Saeedeh Mazinani (Polyolefins Journal, 2023)
The effect of structural defects on graphene interaction with other molecules is of high interest. In this study, the interaction of ethylene molecules with pristine graphene (PG) and defective graphenes including single (SVG) and double (DVG) vacancies, were investigated using dispersion-corrected periodic density functional theory (DFT). We used various pairs of pseudopotentials and dispersion-corrected methods to calculate the exchange-correlation energies and long-range energies, respectively. We conducted the calculations in the ethylene-graphene equilibrium distance where vdW interaction as a long-range interaction was dominant. Both adsorption and deformation energies were calculated to examine the possibility of ethylene chemisorption. It was found that there is a critical distance from the graphene surface, where the nature of adsorption of adsorbate molecule changes from physisorption to the possible chemisorption depending on the energetical costly distortion induced in adsorbate molecule. In the case of ethylene adsorption on the graphene structures studied here, the mentioned critical distances follow the order SVG < DVG < PG. However, in the range of vdW domination and in comparison with PG, ethylene interacts more with SVG due to the presence of a dangling bond and interacts less with DVG due to the presence of a hole. Furthermore, the interactions of ethylene with reconstructed trivacancy were studied. Moreover, all possible orientations for ethylene adsorption on graphene structures were considered and energetically compared. All calculations were done on fully optimized reconstructed geometries of vacancies with structural characteristics, i.e., reconstruction length and formation energies comparable to those reported in the literature.